Head trauma in children - Sapagovaitė, Ingrida; Ravinskienė, Julija (Lietuvos chirurgija, 2015)
BackgroundHead trauma is one of the most common injuries in children. The aim of this article is to review and analyse data on head traumas in children documented in the Children Hospital (2008–2013), their causes, mechanism and nature of lesions and to define the age-related risk groups. To establish the severity of lesions, a ratio of cases treated in an out-patient setting and hospitalisation cases as well as peculiarities of hospitalisations and to compare these data with data from the developed countries available in the publications.Material and methodsStatistical data of children under 18 year-old admitted to the Emergency Department of the Children Hospital due to head trauma within the period of 6 years were analysed. Emergency Department served 100 918 children within the period of 6 years. Head trauma was a reason for consultation in 19970 cases (19.8%). The majority of patients were treated in an outpatient setting. The majority of patients were infants and children under 3 year-old and adolescents above 16 year-old. The mean age of patients was 7 years. 22.2 % of patients (4424 children) were hospitalised. The proportion of hospitalised patients increased with growing age. Girls-boys ratio was 1 : 1.9. Accordingly, hospitalisation ratio was 1 : 2. This ratio varied among the age-groups.ResultsHead contusions (S00) were reported most frequently in small children; the proportion of patients younger than three-year old patients was 45.3%. About half of the cases of cranial fractures have been diagnosed in children younger than one-yearold.Intracranial brain lesions have been more characteristic for children above the age of three years. The main diagnostic tool for the fracture diagnosis is X-ray images. They were performed for 66.5 % of patients. 142 CT imaging procedures (0.9%) were carried out. 888 children (4.45 % of all head trauma cases) were suffering from head trauma acquired in a car accident.Only 1% of case victims of the car accidents were infants and children younger than 1–2 year-old. The majority of children of this age group were the sufferers of domestic traumas.ConclusionWe suggest that considering the age of children, a location, nature and severity of the trauma can be foreseen and prevention measures can be applied. The main activities should be focused on education and teaching of adults aiming to reduce the risk of traumas in the groups of children of certain age and to eliminate their causes.
Keywords: head trauma; head trauma in children; head contusion; head commotion; trauma in children